The Development of Green Technology Model in the Process of Making Gamelan, Klungkung Regency, Bali - I Ketut Gde Juli Suarbawa (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
The work bent on the smelting process which is very low and with the flame still open so that the heat from combustion is wasted into the environment has the potential to pollute the environment and expose the craftsmen to cause an increase in workload, subjective disorders and a decrease in work productivity. For this reason, one short case study was conducted with a pre and pos test group design that was carried out observationally on craftsmen in the bronze smelting process for gamelan raw materials. The workload was predicted by calculating the working pulse, fatigue and complaints of skeletal muscle craftsmen recorded by questionnaire. The results of the research data were analyzed descriptively to obtain a new design of the bronze metal smelting furnace model so that the work attitude was more ergonomic. The results showed that the work pulse increased to 132.42 ± 4.41 per minute or increased by 58.21 beats per minute, including in the category of